2019
DOI: 10.1007/s00181-019-01760-y
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in price responsiveness for residential space heating in Germany

Abstract: SOEPpapers on Multidisciplinary Panel Data Research at DIW Berlin This series presents research findings based either directly on data from the German SocioEconomic Panel study (SOEP) or using SOEP data as part of an internationally comparable data set (e.g. CNEF, ECHP, LIS, LWS, CHER/PACO). SOEP is a truly multidisciplinary household panel study covering a wide range of social and behavioral sciences:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Findings are, however, typically mixed and inconclusive. For example, lower-income consumers sometimes appear to be more responsive to incentives and energy and technology prices (Reiss and White, 2005 ; Alberini et al, 2011 ; Allcott, 2011a ; Ito, 2015 ; Ida et al, 2016 ; DeShazo et al, 2017 ; Houde, 2018 ; Charlier and Kahouli, 2019 ; Lundgren and Schultzberg, 2019 ; Schmitz and Madlener, 2020 ), but other studies disconfirm or qualify this link (Nesbakken, 1999 ; Herter, 2007 ; Faruqui et al, 2013 ; Moshiri, 2015 ; Zhang, 2015 ; Schulte and Heindl, 2017 ; Hansen, 2018 ; Alberini et al, 2019 ; Harding et al, 2020 ; Prest, 2020 ). Inconsistent findings could be partly due to methodological differences across studies or context-dependency of the effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings are, however, typically mixed and inconclusive. For example, lower-income consumers sometimes appear to be more responsive to incentives and energy and technology prices (Reiss and White, 2005 ; Alberini et al, 2011 ; Allcott, 2011a ; Ito, 2015 ; Ida et al, 2016 ; DeShazo et al, 2017 ; Houde, 2018 ; Charlier and Kahouli, 2019 ; Lundgren and Schultzberg, 2019 ; Schmitz and Madlener, 2020 ), but other studies disconfirm or qualify this link (Nesbakken, 1999 ; Herter, 2007 ; Faruqui et al, 2013 ; Moshiri, 2015 ; Zhang, 2015 ; Schulte and Heindl, 2017 ; Hansen, 2018 ; Alberini et al, 2019 ; Harding et al, 2020 ; Prest, 2020 ). Inconsistent findings could be partly due to methodological differences across studies or context-dependency of the effects.…”
Section: Resultsmentioning
confidence: 99%
“…(f) Baseline behavior levels. Findings concerning responsiveness to energy prices of households with different consumption levels are mixed (Herter, 2007 ; Kaza, 2010 ; Gilbert and Graff Zivin, 2014 ; List et al, 2017 ; Royal and Rustamov, 2018 ; Harding et al, 2020 ; Prest, 2020 ; Schmitz and Madlener, 2020 ; Todd-Blick et al, 2020 ; Murakami et al, 2022 ). This could be partly due to context- or behavior-specificity of the effects (see Kaza, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…Their results are confirmed by Frondel et al (2015), who studied the inequality in electricity price burden of German households. Schmitz and Madlener (2020) use the dataset used in our analysis to estimate elasticity of heating consumption to a change in prices for different groups. They find that wealth and home-ownership lead to a lower price responsiveness and find a U-shaped elasticity across consumption deciles indicating that families spending the average amount on gas are the least reactive to heat cost shocks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, we assume 50 percent fix costs that cannot be reduced by individual behavior. Second, we apply gas price elasticities by gas expenditure quantiles, provided by (Schmitz and Madlener, 2020) for Germany. The study finds relatively stable estimates, where a 1 percent increase in gas prices reduces the gas expenditures by -0.33 for the lowest quantile, and -0.36 for the median.…”
Section: Distributional Effect Of the Natural Gas Price Increasementioning
confidence: 99%
“…It was observed that socioeconomic changes had little effect on energy costs, but dwelling size had a significant effect on energy costs. Schmitz and Madlener (2016) investigated the effects of sociodemographic variables such as age and gender on building types and technical characteristics in explaining the heating costs of houses. One of the important findings is that the heating cost rate of low-income dwellings is higher than the dwellings with high income levels.…”
Section: Introductionmentioning
confidence: 99%